Compared with Powdered Lutein, a Lutein Nanoemulsion Increases Plasma and Liver Lutein, Protects against Hepatic Steatosis, and Affects Lipoprotein Metabolism in Guinea Pigs. Issue 10 (31st August 2016) - Murillo, Ana Gabriela; Aguilar, David; Norris, Gregory H; DiMarco, Diana M; Missimer, Amanda; Hu, Siqi; Smyth, Joan A; Gannon, Sarah; Blesso, Christopher N; Luo, Yangchao; Fernandez, Maria Luz
Abstract: Background: It is not clear how oil-in-water nanoemulsions of lutein may affect bioavailability and consequently alter lipoprotein metabolism, oxidative stress, and inflammation. Objective: The bioavailability as well as effects of a powdered lutein (PL) and an oil-in-water lutein nanoemulsion (NANO; particle size: 254.2 nm; polydispersity index: 0.29; and ζ-potential: −65 mV) on metabolic variables in liver, plasma, and adipose tissue in a guinea pig model of hepatic steatosis were evaluated. Methods: Twenty-four 2-mo-old male Hartley guinea pigs, weighing 200–300 g ( n = 8/group), were fed diets containing 0.25 g cholesterol/100 g to induce liver injury for the duration of the study. They were allocated to control (0 mg lutein), PL (3.5 mg/d), or NANO (3.5 mg/d) groups. After 6 wk, plasma, liver, and adipose tissue were collected for determination of lutein, plasma lipids, tissue cholesterol, and inflammatory cytokines. Results: The NANO group had 2-fold higher concentrations of lutein in plasma ( P < 0.001) and 1.6-fold higher concentrations in liver ( P < 0.001) than did the PL group, indicating greater bioavailability of this carotenoid. The NANO group also had 24% lower hepatic steatosis scores ( P < 0.05), 31% lower hepatic cholesterol accumulation ( P < 0.05), and 64% lower plasma alanine aminotransferase ( P < 0.05) than did the control group. Hepatic oxidized LDL was 55% lower in both the PL and NANO groups than in the control group ( P < 0.05). In plasma, the NANO group had 2-fold higher concentrations of LDL and HDL cholesterol as well as a 2-fold higher number of VLDL, LDL, and HDL particles than did the other 2 groups as evaluated by nuclear magnetic resonance. Furthermore, the NANO group had 15% higher concentrations of free cholesterol in adipose tissue, resulting in higher concentrations of inflammatory markers, than did the other 2 groups. Conclusions: These results indicate that, although this lutein nanoemulsion exerted protective effects against hepatic steatosis, plasma lipoproteins and adipose tissue cholesterol were increased. These data suggest that the metabolic effects of this particular nanoemulsion might not be protective in all tissues in guinea pigs.